2. Rezolvă: 4 x 6:3= = (12 + 3 + 6): 3 = 39 - 12:3+ (7 + 14) : 7 = 2 x 9 + 16 : 4 =
Anexe:
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
Explicație pas cu pas;
4 × 6 : 3 = 24 : 3 = 8
2 × 9 + 16 : 4 = 18 + 4 = 22
(12 + 3 + 6) : 3 = 21 : 3 = 7
39 - 12 : 3 + (7 + 14) : 7 = 39 - 4 + 21 : 7 = 35 + 3 = 38
lidlromania:
mss
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă